Vocal Fold Cancer Transoral Laser Microsurgery Following European Laryngological Society Laser Cordectomy Classification - Mendelsohn, Abie H.; Remacle, Marc Joseph (Frontiers in Oncology, 2018)
Background: The surgical treatment of glottic, or vocal cord, cancer has seen considerable progression over the past several decades. Specifically, there has been a stark transition from open partial laryngectomy surgery to endoscopic laser microsurgical techniques which have been inspired in large part by two landmark studies: Professor Wolfgang Steiner’s original case series describing transoral laser microsurgery for glottic cancer (1993) and the European Laryngological Society’s (ELS) classification scheme (2000). We performed a comprehensive review of published literature to characterize the pattern of this novel modality as compared with two landmark studies over the past four decades. Methods: An English literature search was conducted on PubMed for available original investigations on surgical treatment of glottic laryngeal cancer published over the past 40 years. Our Boolean criteria included the following terms: cancer, glottic, laryngeal, surgery, endoscopic, and laser. The publication rates were calculated as annual compound growth as well as corrected growth rates as defined by the Fisher equation for inflation effects. Results: Our review identified 13,372 studies covering Larynx Cancer and 3,557 studies covering Glottic Cancer original studies. Among these, we analyzed the compound annual growth rates and correct growth rates for three distinct publication periods or epochs, prior to 1993, 1993-1999, and 2000-2017. For all but two of the search term groups covering both Glottic Cancer as well as Larynx Cancer, there was a substantial growth improvement in the time period following the ELS classification scheme as compared with the growth rate of the time period following Steiner’s case series. Conclusion: The progress towards minimally invasive treatment of glottic cancer has progressed steadily over the past several decades. Analysis of publication show increased growth during the time period following the ELS classification scheme over the time period following Steiner’s landmark study. A mistake would be concluding any diminished importance of Professor Steiner’s work, instead, our analysis demonstrates the wide-spread adoption of the endoscopic laser cordectomy procedure following the ELS classification system. Complex surgical techniques such as transoral laser microsurgery are optimally disseminated within well-defined classification schemes, though further validation is warranted.